2022
DOI: 10.3389/fpsyt.2022.1008290
|View full text |Cite
|
Sign up to set email alerts
|

Attention–deficit/hyperactivity disorder symptoms, perceived stress, and suicidal ideation during the COVID-19 pandemic

Abstract: ObjectiveAttention–deficit/hyperactivity disorder (ADHD) symptoms have been linked to suicidal behavior. However, little is known about the mechanisms involved in this association. This study examined ADHD symptoms and suicidal ideation during the COVID-19 pandemic and the role of self–perceived stress in this association.MethodData were analyzed from an online sample of 1,452 Japanese individuals aged 18 to 89 obtained in February 2021. Information was collected on past–year suicidal ideation. ADHD symptoms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…[65] The crusade in the search to minimize the evils of neurodegenerative diseases ranges or computing resources from the search for possible correlated microorganisms to dysfunctional behavioral patterns and biomarkers. [66][67][68][69] The more we study AD we realize that the breadth of the topic requires the formation of multidisciplinary teams for research. [70] No matter how distant computer science may seem from philosophy, from genetics to psychology, everything is connected in the search for better aging.…”
Section: Discussionmentioning
confidence: 99%
“…[65] The crusade in the search to minimize the evils of neurodegenerative diseases ranges or computing resources from the search for possible correlated microorganisms to dysfunctional behavioral patterns and biomarkers. [66][67][68][69] The more we study AD we realize that the breadth of the topic requires the formation of multidisciplinary teams for research. [70] No matter how distant computer science may seem from philosophy, from genetics to psychology, everything is connected in the search for better aging.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested a negative psychological impact of the COVID-19 pandemic quarantines on mental health of the paediatric population worldwide, with an increasing number of the reported new diagnosis of mental disorders in children and adolescents over time since the outbreak in March 2020 [5][6][7][8][9][10][11]. Anxiety, depression, sleep disorders, and eating disorders resulted to be among the leading causes of illness and disability in this population [12][13][14][15][16][17][18][19][20][21]. Moreover, children with pre-existing behavioral disorders, such as autism spectrum disorders or ADHD had a high probability of worsening of their behavioral symptoms, probably also due to difficulties in accessing to child neuropsychiatry support services for pandemic containment measures [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Comorbid substance use disorders significantly potentiated the risk of severe COVID-19 ( 14 ). Beyond that, perceived stress increased the risk for suicidal ideation in individuals with ADHD symptoms in an adult Japanese sample ( 15 ).…”
Section: Introductionmentioning
confidence: 99%